TINJAUAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO. 16 TENTANG AKTIVA TETAP PADA PT. SUKSES TANI NUSA SUBUR PENAJAM PASER UTARA - -, Nurul Zanah (EKONOMIA, 2014)
This study aims to determine the extent to which the company applies the theory of SFAS No. 16, on the valuation of fixed assets in the financial statements PT.Sukses Tani Nusasubur.The problem of this study is,